Panoptic Variations: Surveillance and Discipline in Web Courses - Roger Boshier; Mary Wilson (Adult Education Research Conference, 1998)
Disciplinary surveillance nested in some Web courses violates principles of adult education. Using Foucault’s notion of panopticism, the authors present a model that can be used to determine levels of disciplinary surveillance.